(untitled) (CIPEEX, 2025)
In recent decades, increased life expectancy has resulted in a growing elderly population, highlighting the importance of interventions that promote the health and independence of older adults. Strength training has emerged as an effective strategy to improve the quality of life in this age group. Objective: This bibliographic review article aims to identify and analyze the benefits of strength training for the elderly, based on studies published in electronic databases and specialized literature. Methods: Scientific articles and books addressing strength training in the elderly were reviewed. Sources were selected from databases such as BIREME, CAPES, LILACS, and SCIELO, covering publications from 2019 to 2024. Results: The review revealed several benefits of strength training for the elderly, including: • Increased Muscle Strength and Power: Improves the ability to perform daily activities and reduces the risk of falls. • Improved Body Composition: Increases muscle mass and reduces body fat. • Functional Capacity: Facilitates the execution of daily tasks and physical activities. • Reduced Risk of Chronic Diseases: Helps control diseases such as diabetes, hypertension, and osteoporosis. • Mental Health: Promotes psychological well-being, reducing symptoms of depression and anxiety. Conclusion: Strength training is an effective intervention to promote the health and independence of the elderly. Studies indicate that individualized approaches tailored to the specific needs of each elderly person are essential to achieve satisfactory results. The implementation of strength training programs should be encouraged as part of a comprehensive public health strategy for the elderly population.